OF THE POSSIBILITY TO ADMINISTER THE ANTIINFLAMMATORY MEDICATION THROUGH A NEBULISER DURING ACUTE OF BRONCHIAL ASTHMA AMONG CHILDREN - R.M. Torshkhoeva; E.A. Vishneva; A.A. Alekseeva; L.S. Namazova (Union of pediatricians of Russia, 2007)
The research is dedicated to the efficiency evaluation of the budesonide based nebuliser therapy to reduce the exacerbation of bronchial asthma among children and teenagers. it was uncovered that the efficiency of such therapy reached 100%, which is manifested both in the decrease of the symptomatology intensity and improvement for the indices of the external respiration function, while there are no side effects whatsoever.Key words: bronchial asthma, budesonide, nebuliser, children.